How to boost the European Green Deal's scale and ambition - Rafael Wildauer; Stuart Leitch; Jakob Kapeller (Universität Duisburg-Essen, Institut für Sozioökonomie (ifso), 2020)
The European Green Deal (EGD) is the European Union's flagship strategy to tackle climate change. This policy study compares the ambition and scale of the EGD with the current relevant scientific literature. The goal is to assess whether the current proposals are capable of fulfilling the EU's commitment to limit global warming to 1.5°C in line with the Paris Agreement. (...) Taken together, this suggests that annual investment requirements of up to exteuro 855 billion (excluding transport) in the EU27 would be required for a successful transition. Setting and delivering on more ambitious GHG emission reduction targets requires the use of all possible policy tools. The EGD is a promising start in this context as it relies on a broad set of instruments from regulations, carbon markets, taxes and public investment. Given the limited time available however the EGD should go a step further and upgrade the Sustainable Europe Investment Plan into a comprehensive climate master plan which determines clear targets and timelines for renewable energy capacity, building renovations, transport infrastructure, R&D targets etc. This would not only provide the private sector with clear long-term signals but also allow for timely monitoring of the EU's progress.
Keywords: 330